Electroacupuncture attenuates retinal ischemia/reperfusion injury by protecting the outer blood-retina barrier via enkephalins activate delta opioid receptor - Ping CHEN; Xian-dan ZHU; Run-jie GUO; Yong XIA; Jing-ling JIN; Nan-ge JIN; Ying-min GU; Xue-song TIAN (World Journal of Acupuncture - Moxibustion)
Objectives: Retinal ischemia-reperfusion (RIR) injury results in irreversible visual impairments. The disruption of the outer blood-retinal barrier (OBRB) is a major ocular pathogenic process that RIR injury affects. Current clinical strategies are limited. This study aimed to elucidate how electroacupuncture (EA) protects the OBRB against RIR injury. Methods: Male Wistar rats (7 weeks old, 250 g to 280 g) were used in this study. Three independent experiments were conducted. First, Opioid peptide levels were quantified using enzyme-linked immunosorbent assay (ELISA). 42 rats were randomly divided into 7 groups (n = 6/group): Control: No treatment; high intraocular pressure(HIOP): Acute intraocular pressure elevation-induced RIR injury; HIOP + SHAM EA: RIR injury + sham EA at Xinming (Extra acupoint) and Jingming (BL1) for 30 min (shallow needle insertion but without electric stimulation); HIOP + 2 Hz EA: RIR injury + 2 Hz EA at Xinming and BL1 for 30 min; HIOP +100 Hz: RIR injury + 100 Hz EA at Xinming and BL1 for 30 min; HIOP + 2/100 Hz EA: RIR injury + 2/100 Hz EA at Xinming and BL1 for 30 min; HIOP + 4/20 Hz EA: RIR injury + 4/20 Hz EA at Xinming and BL1 for 30 min. Second, retinal morphology was assessed by hematoxylin and eosin (HE) staining. 20 rats were randomly allocated into 4 groups (n = 5/group): Control: No treatment; HIOP: Acute intraocular pressure elevation-induced RIR injury; HIOP + SHAM EA: RIR injury + sham EA at Xinming and BL1 for 30 min (shallow needle insertion but without electric stimulation); HIOP + 2 Hz EA: RIR injury + 2 Hz EA at Xinming and BL1 for 30 min. Third, the permeability of OBRB was evaluated using the fluorescein isothiocyanate(FITC)-dextran leakage assay. 15 rats were randomly divided into 5 groups (n = 3/group): Control: No treatment; HIOP: Acute intraocular pressure elevation-induced RIR injury; HIOP + SHAM EA: RIR injury + sham EA at Xinming and BL1 for 30 min (shallow needle insertion but without electric stimulation); HIOP + 2 Hz EA: RIR injury + 2 Hz EA at Xinming and BL1 for 30 min; Nal + HIOP + 2 Hz EA: Intravitreal injection of δ-opioid receptor antagonist Naltridole (10µl, 100 nM) 30 min before RIR injury induction, followed by 2 Hz EA treatment at Xinming and BL1 for 30 min. In vitro studies examined enkephalins' effects on oxygen–glucose deprivation /reperfusion (OGD/R) induced injury in ARPE‐19 cells. Cell viability was evaluated by cell counting kit-8 (CCK-8) assay, and morphological changes were recorded by Molecular Devices. Apoptosis was detected by Annexin V-FITC flow cytometry. Delta opioid receptor (DOR) expression in total protein and membrane protein were analyzed by western blotting (WB). Immunofluorescence (IF) staining and WB assessed ZO-1 and Claudin-19. For cell-based assays, n indicates the number of biologically independent replicates. Results: It was found that 2 Hz EA treatment increased enkephalins (methionine-enkephalin and leucine-enkephalin) levels (P < 0.01), restoring the increased retinal thickness (P < 0.05) and mitigating RGCs loss (P < 0.05) post-RIR injury. FITC-dextran leakage in the outer retina was ameliorated by 2 Hz EA (P < 0.05), reversibly countered by Naltrindole(P < 0.05), a DOR antagonist. Treatment with 30 µM enkephalins enhanced ARPE-19 cell viability (P < 0.001, P < 0.0001) and inhibited apoptosis (P < 0.0001). Enkephalins elevated DOR levels in total protein (P < 0.05) and membrane protein fractions (P < 0.001, P < 0.0001), as well as elevated ZO-1 (P < 0.001, P < 0.01) and Claudin-19 (P < 0.0001, P < 0.001) levels following OGD/R, counteracted by Naltrindole. Conclusion: It was found that 2 Hz EA inhibits the breakdown of OBRB via enkephalins activate DOR in RIR injury.